Creative tourism development through storynomics tourism model in Borobudur - Lintang Citra Christiani; Prinisia Nurul Ikasari; Fitria Khairum Nisa (Faculty of Communications Science, Dr. Soetomo University, 2022)
So far, the development of tourism in Borobudur depends on The Borobudur Temple as a tourist destination. Meanwhile, sustainable tourism, can’t only promote destinations, but also the strengthening of environmental sustainability, local wisdom, and sustainable economy. This study aims to explain the development of creative tourism through the model of storynomics tourism in Borobudur. The concept used in this research include creative tourism, storytelling in marketing communication, and storynomics tourism model. This research applies both quantitative and qualitative approach. Data collection was done through a survey, FGD, and interview. The result show that there are at least five sources of tourism creativity in Borobudur, namely creativity in nature, arts/craft, spirituality, gastronomy, and language. The creativity comes from collaboration between government, local communities, tourism service provider, and the tourism themselves. The development of creative tourism is done with the formation of cultural narrative that originates from culture, history, and relief of Borobudur Temple into story of economic value (storynomics). Should be italic